Sistem Informasi Berbasis Web Soto Kudus Kembang Joyo - Muhammad Suparmono Mono; Andi Saryoko; Ganda Wijaya (LPPM Universitas Bina Sarana Informatika, 2020)
The development of the technological world provides for humans in carrying out business transactions. With the existence of business process information systems or can be more efficient and effective. Soto Kudus still uses manual paper records in its business processes, so that data requests are less effective which causes data manipulation, and there are no web-based monitoring charts. By implementing a web-based information system, it is expected to be able to provide convenience in running business processes. The programming language used is using the PHP programming language with a codeigniter framework. For storing data, the author uses Mysqli. The results of this application to facilitate the admin in processing data and facilitating management in monitoring sales data charts, as well as saving paper usage and sales data security